THE IMPORTANCE OF DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF FINE ARTS IN THE HIGHER EDUCATION SYSTEM (Scientific journal of the Fergana State University, 2024)
This article presents an analysis of opinions aimed at reforming the education system, expanding coverage of modern trends, and improving the quality of personnel. In the process of enriching the curriculum with subjects in modern academic disciplines, modern students suggest keeping up with the process of introducing the concept of artificial intelligence and its use in the process of globalization.